2014
DOI: 10.1002/jbt.21570
|View full text |Cite
|
Sign up to set email alerts
|

Modulator Effects of Meloxicam against Doxorubicin-Induced Nephrotoxicity in Mice

Abstract: Doxorubicin-induced renal toxicity overshadows its anticancer effectiveness. This study is aimed at assessing the possible modulator effects of meloxicam, a cyclooxigenase-2 inhibitor, on doxorubicin-induced nephrotoxicity in mice and exploring some of the modulator mechanisms. Forty male mice were divided for treatment, for 2 weeks, with saline, meloxicam (daily), doxorubicin (twice/week), or both meloxicam and doxorubicin. Doxorubicin induced a significant increase in relative kidney weight to body weight, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 65 publications
3
14
0
Order By: Relevance
“…54,58 By activating caspase-3 in renal proximal tubular cells and causing mitochondrial pathway, DOX probably leads apoptosis, which can arise renal cell damage and disorganized renal histology. 59 In present study, under the pretreatment of YQFM, expressions of BAX/Bcl-2 ratio, caspase-3 and cytochrome c were quite reduced, and then the inhibition of apoptosis could prevent tissue lesions and dysfunction, which was associated to the effect of ginsenosides included in YQFM. 38,60…”
Section: Discussionmentioning
confidence: 49%
“…54,58 By activating caspase-3 in renal proximal tubular cells and causing mitochondrial pathway, DOX probably leads apoptosis, which can arise renal cell damage and disorganized renal histology. 59 In present study, under the pretreatment of YQFM, expressions of BAX/Bcl-2 ratio, caspase-3 and cytochrome c were quite reduced, and then the inhibition of apoptosis could prevent tissue lesions and dysfunction, which was associated to the effect of ginsenosides included in YQFM. 38,60…”
Section: Discussionmentioning
confidence: 49%
“…They also have, antioxidant effect, and free radical scavenging activity. [58] These findings further strengthen the interest to biological activity and The compounds were applied at a concentration of 500 mg/mL. DMSO-control cells were cultured in a medium containing 2% DMSO.…”
Section: Long-term Experimentsmentioning
confidence: 73%
“…TNF‐α has importance in initiation and regulation of cytokine cascade in immune response process (Kuzu et al, ). Also, several studies have reported that COX‐2 increases TNF‐α production (Benzer et al, ; Caglayan, Temel, Kandemir, Yildirim, & Kucukler, ; Hassan, Ghobara, & Abd‐Allah, ). We found that rutin decreased TNF‐α and COX‐2 expression levels dose‐dependently.…”
Section: Discussionmentioning
confidence: 99%